Primary Breast Augmentation with Silicon Implant - Jung Basnet, Surendra; Kumar Nagarkoti, Krishna; Amatya, Sudeep; Tripathee, Sanjib (Annapurna Journal of Health Sciences, 2023)
Introduction: Breast augmentation remains one of the most commonly performed cosmetic procedures. It is a surgery of breast in order to increase its size by placing breast implants under breast tissue or chest muscles. Silicon implant is used for both cosmetic and reconstructive reasons. The purpose of this study was to evaluate the outcomes of primary breast augmentation with silicon implant. Methods: A retrospective study was performed in patients who underwent silicon based breast augmentation through inframammary in submuscular dual plane, between February 2017 and January 2019. Surgical outcomes were evaluated and Patient satisfaction was measured using the BREAST-Q Augmentation Module. Results: This study involved a total of 32 patients (i.e. 64 breasts),19 patients were mongoloid and 12 were non mongoloid. The average age was 32.25 years (range: 20-45 years) between a follow up period of 24 months.The size of breast implant ranged from 240-340 cc. Thirty-one patients were satisfied with the outcome. Seroma was noted in two patients. One of the patients was not satisfied and was noted with capsular contracture within follow-up period. Fifteen patients were used with implant size 280 cc. All patients were able to go to normal daily activity after seventh post-operative day. Conclusion: Breast augmentation with silicon implant have potential to produce more satisfactory and aesthetically pleasing results with low revision rates. Even though various techniques are existing in breast augmentation but still universal standard technique is controversial.